Empowering Educational Autonomy to Implement Kurikulum Merdeka in Madrasah - Hilda Ainissyifa; Yufi Mohammad Nasrullah; Nurul Fatonah (Jurnal Pendidikan Islam, 2024)
This study investigated the pivotal role of education management in the implementation of the Kurikulum Merdeka (KM) within Madrasah institutions. Grounded in Terry's management functions theory, the research discerns both the facilitating factors and obstacles encountered during the curriculum implementation. Employing qualitative methodologies, including interviews with madrasah heads, teachers, and students, alongside curriculum document analysis, the study unfolds crucial insights. The findings underscore the indispensable nature of effective education management across the phases of planning, execution, and evaluation of the KM Supportive elements encompass stakeholder engagement, provision of adequate facilities, and the adoption of flexible learning methodologies. Conversely, significant challenges emerge, such as the imperative for enhanced comprehension of KM and the necessity for gradual readiness in its implementation. This research extends its contribution by delineating actionable strategies to surmount these obstacles, thereby furnishing guidance for madrasahs and other educational institutions in navigating KM implementation. These insights hold promise for enhancing the efficacy of curriculum deployment at the madrasah level, while also paving the way for further exploration within the Indonesian educational landscape.